### 1 Answer

- 土扁Lv 75 years agoFavorite Answer
5.

(a)

(5 / 4c) - (1 / 5c)

= (25 / 20c) - (4 / 5c)

= (25 - 4) / 20c

= 21 / 20c

(c)

(5 / 8a) - (5 / 6a)

= (15 / 24a) - (20 / 24a)

= (15 - 20) / 24a

= 5 / 24a

(d)

(u / 3v) + (2u / 5v)

= (5u / 15v) + (6u / 15v)

= (5u + 6u) / 15v

= 11u / 15v

====

6.

(a)

[2 / (a + 1)] + [10 / (a + 1)]

= (2 + 10) / (a + 1)

= 12 / (a + 1)

所以 ( ) = 12

(b)

(3b / 5c) - [( ) / 5c] = b / 5c

3b - ( ) = b

所以 ( ) = 2b

(c)

[( ) / (2d + e)] - [2d / (2d + e)] = 1 / (2d + e)

( ) - 2d = 1

所以 ( ) = 2d + 1

(d)

[( ) / (f - g)] - [f / (f - g)] = 2g / (f - g)

( ) - f = 2g

( ) = f + 2g

====

7.

(a)

[8 / (7m - n)] - [1 /(n - 7 m)]

= [8 / (7m - n)] + [1 /(7 m - n)]

= (8 + 1) / (7m - n)

= 9 / (7m - n)

(b)

[p / (p - 6)] + [6 / (6 - p)]

= [p / (p - 6)] - [6 / (p - 6)]

= (p - 6) / (p - 6)

= 1

(c)

[(w + l) / (wl - 1)] - [(w - l) / (1 -wl)]

= [(w + l) / (wl - 1)] + [(w - l) / (wl - 1)]

= [(w + l) + (w - l)] / (wl - 1)

= (w + l + w - l) / (wl - 1)

= 2w / (wl - 1)

(d)

[2x / (3x + y)] - [(x + y) / (-y - 3x)]

= [2x / (3x + y)] + [(x + y) / (y + 3x)]

= [2x / (3x + y)] + [(x + y) / (3x + y)]

= [2x + (x + y)] / (3x + y)

= (2x + x + y) / (3x + y)

= (3x + y) / (3x + y)

= 1

====

8.

(a)

[1 / (3 + x)] + [7 / 4(3 + x)]

= [4 / 4(3 + x)] + [7 / 4(3 + x)]

= (4 + 7) / 4(3 + x)

= 11 / 4(3 + x)]

(b)

[3 / 2(a + b)] + [5 / (a + b)]

= [3 / 2(a + b)] + [10 / 2(a + b)]

= (3 + 10) / 2(a + b)

= 13 / 2(a + b)

(c)

[3x / (x - 6)] - [x / 5(x - 6)]

= [15x / 5(x - 6)] - [x / 5(x - 6)]

= (15x - x) / 5(x - 6)]

= 14x / 5(x - 6)

(d)

[(3b + 1) / 2(a + b)] - [2b / (a + b)]

= [(3b + 1) / 2(a + b)] - [4b / 2(a + b)]

= [(3b + 1) - 4b] / 2(a + b)]

= (3b + 1 - 4b) / 2(a + b)]

= (1 - b) / 2(a + b)